Saposhnikovia divaricata root and its major components ameliorate inflammation and altered gut microbial diversity and compositions in DSS-induced colitis - Saruul Erdenebileg; Yang-Ju Son; Myungsuk Kim; Sarangerel Oidovsambuu; Kwang Hyun Cha; Jaeyoung Kwon; Da Seul Jung; Chu Won Nho (Integrative Medicine Research, 2023)
Background: The root of Saposhnikovia divaricata (Turcz.) Schischk is a well-known traditional medicinal plant, containing various bioactive compounds with anti-inflammatory, antioxidant, and analgesic properties. However, no scientific studies have validated its clinical use as an anti-inflammatory agent against inflammatory bowel disease (IBD). This study aimed to investigate whether the root extract of S. divaricata ameliorates IBD and induces gut microbial alteration, using a RAW 264.7 cell line and a DSS-induced colitis mouse model. Methods: To investigate the anti-inflammatory effects and alleviation of IBD, using a methanol extract of Saposhnikovia divaricata (Turcz.) Schischk. root (MESD), RAW 264.7, murine macrophages and a dextran sodium sulfate (DSS)-induced colitis mouse model were employed. 16S rRNA gene sequencing was conducted to determine the alterations in the gut microbiota of mice with DSS-induced colitis. Results: MESD significantly decreased nitric oxide (NO) and inflammatory cytokine levels in lipopolysaccharide (LPS)-induced RAW 264.7 cells in vitro. Oral administration of MESD reduced the expression of inflammatory cytokines in the colons of mice with DSS-induced colitis. Additionally, MESD inhibited the abundance of Clostridium sensu stricto 1 and enhanced the predicted functional pathways, including l-glutamate degradation VIII (to propanoic acid). Seven compounds with anti-inflammatory properties were isolated from the MESD. Among them, 3′-O-acetylhamaudol and 3′-O-angeloylhamaudol exhibited strong anti-inflammatory effects in vitro. Conclusion: Overall, MESD may be a potential natural product for the treatment of IBD by lowering inflammatory cytokine levels and altering gut microbiota composition.